A case of visceral leishmaniasis imported from Armenia - A. L. Rossina; S. B. Chuelov; N. V. Kondratenko; E. V. Tselovalnikova; A. V. Tebenkov; S. V. Kolyagina; N. A. Sokolova; N. V. Nepokulchitskaya (LLC "Diagnostics and Vaccines", 2023)
The relevance of the problem of visceral leishmaniasis is due to the severity of clinical manifestations, as well as the need for immediate etiotropic therapy. The aim of the work is to summarize the data available in the literature regarding the epidemiological situation of visceral leishmaniasis in the Republic of Armenia, taking into account the possibility of imported cases in the territory of the Russian Federation. Materials and methods: a review of domestic and foreign literature over the past 10 years, including Internet resources, was carried out and our own clinical observation of a child with relapsed visceral leishmaniasis imported from Armenia was presented. Conclusion. Visceral leishmaniasis is endemic for Transcaucasia, incl. for the Republic of Armenia, disease. Persons who have visited areas of high risk of infection with developed characteristic symptom complex, including fever, hepatosplenomegaly, pancytopenia, are subject to examination for visceral leishmaniasis. After the treatment, it is necessary to carry out dynamic monitoring.